TRANSFORMATIONAL LEADERSHIP PRACTICES OF SCHOOL HEADS AND PERFORMANCE OF CITY SCHOOLS IN THE DIVISION OFFIRST DISTRICT OF LAGUNA, PHILIPPINES - Buenvinida, Lerma P; Ramos, Ma. Theresa S (PEOPLE: International Journal of Social Sciences, 2019)
A study was conducted to determine the transformational practices of school leaders of city schools in the Division of First District of Laguna, Philippines. Further, the research aimed also to determine the extent of transformational leadership practices among public elementary school heads and teachers in terms of: Idealized Influence,Inspirational Motivation,Intellectual Stimulation and Individualized Consideration; assessed the performance of public elementary schools in terms of: Drop Out Rate , Cohort Survival Rate, Completion Rate, and Achievement Rate and determined the significant relationship between transformational leadership practices and the performance of public elementary schools. The descriptive correlational research design was employed and involved 44 school heads and 591 public elementary teachers. All the practices were assessed by the teacher respondents as highly observed. The schools’ Drop-out rate andCohort Survival Rate with an average of 2.49 and 84.82% respectively were interpreted as Very Satisfactory; and Completion rate of 94.5% as Outstanding. The schools’ National Achievement Test (NAT )is interpreted as Average Proficiency Level.Further studies could be conducted in other districts of Laguna and Region IV-A in order to verify the results as well as to develop a comprehensive training program for teachers as part of the School Improvement Plan.